Principal Transformational Leadership in Increasing Teacher Motivation in Schools - Amarta, Yoga; Zakiya, Nabila; Gistituati, Nurhizrah (Postgraduate School, Universitas Negeri Padang, 2023)
Currently, the teaching and learning process is still becoming an issue that is faced in Indonesian education. The teaching and learning process is still centered on the teacher, and there is a lack of innovation and creativity from the teacher to involve students in building their knowledge. For the teachers to be encouraged to innovate in the learning process, work motivation is needed. The work motivation of the teacher will certainly affect the teacher's performance in learning outcomes and the quality of learning. One effort to increase teacher motivation is through support from the principal. The principal must know and understand the factors that cause the low motivation of each teacher. The principal must start by establishing communication with each teacher to identify the source of the problem of low motivation. As one of the solutions to increase teacher work motivation is the implementation of transformational leadership. Transformational leadership is a leadership theory that has the goal of changing into a leadership theory that can be implemented by school principals in solving problems related to teacher work motivation in schools.